2015
DOI: 10.1055/s-0034-1392328
|View full text |Cite
|
Sign up to set email alerts
|

Forceps versus snare polypectomies in colorectal cancer screening: are we adhering to the guidelines?

Abstract: This study confirmed the importance of the European guidelines. The inclusion of adequate resection technique as a quality indicator in colorectal cancer screening programs is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
3
13
0
1
Order By: Relevance
“…Studies prior to the issuing of the guidelines show a significantly higher rate of inappropriate forceps use, sometimes as high as 46%; studies show a decrease of 14.2% in inappropriate forceps use in hospitals since the new guidelines came into place [3]. This is in keeping with our data.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Studies prior to the issuing of the guidelines show a significantly higher rate of inappropriate forceps use, sometimes as high as 46%; studies show a decrease of 14.2% in inappropriate forceps use in hospitals since the new guidelines came into place [3]. This is in keeping with our data.…”
Section: Discussionsupporting
confidence: 90%
“…The adenoma (as well as the serrated adenoma sequence of colorectal carcinogenesis) lends itself to screening and surveillance, albeit at differing intervals [2]. Studies have shown that the complete removal of colonic polyps during colonoscopy reduces the incidence of CRC [3]. It has also been estimated that incomplete resection is involved in 19–31% of interval cancers [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Austrian hospitals shows that adherence to the guidelines for colorectal cancer screening was worse among private hospitals. After the implementation of a guideline for colorectal screening, only 3.8% of private hospitals changed their routine practice versus 14.2% of public hospitals …”
Section: Resultsmentioning
confidence: 99%
“…After the implementation of a guideline for colorectal screening, only 3.8% of private hospitals changed their routine practice versus 14.2% of public hospitals. 56…”
Section: Processmentioning
confidence: 99%